Різновиди форм і декору тарілок старого українського фарфору Волині з колекції Національного музею українського народного декоративного мистецтва - Титаренко, Анна; Titarenko, Anna (My University, 2013)
Статтю присвячено дослідженню тарілок, які виготовляли фарфоро-фаянсові підприємства Волині в кінці XVTII - на початку XX ст. Розглянуто історію їх виникнення, класифікацію за розмірами та варіативність оздоблення. Проаналізовано особливості декору, притаманного безпосередньо українським виробництвам.The article devoted to research of plates, dishes, saucers made at porcelain and faience enterprises of Volyn region in the end of XVIII - beginning of XX century. It is also reviewed the history of their origin, classification in accordance with sizes and variability of decorating. Considerable attention is given to the characteristic features of the spatial organization of forms and pictorial design, which was created by using of different vegetable, floral, geometric, heraldic motives and elements. Educed and described in detail the most often used types of decor, and also the original untypical kinds of decorations of objects. It is analyzed peculiarities of decoration of typical products of Ukrainian enterprises.
Variety of Forms and Decoration of Plates of Old Ukrainian Porcelain of Volyn from NUFDAM Collection
Keywords: тарілка; оздоблення; український фарфор; кінець XVІІІ – початок XХ століття; Волинь; plate; decoration; Ukrainian porcelain; the end of XVIII - beginning of XX century; Volyn